2010
DOI: 10.1007/s00508-010-1490-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recanalization of internal carotid artery occlusion

Abstract: We present a case of spontaneous recanalization of the internal carotid artery (ICA) that occurred in a 51-year-old male patient. The occlusion of the right ICA was asymptomatic and was detected incidentally during imaging of the opposite carotid artery. The patient underwent neuroradiologic analysis and a tapered, flame-like occlusion suggestive of the right ICA dissection was detected. One month later, a carotid Doppler ultrasound demonstrated patent right carotid artery with normal spectral flow. Five-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, spontaneous recanalization (SR) may occur in patients with ICA occlusion, which may be further categorized as early or late SR, based on the cut-off duration of the mean hospitalization of these patients (usually two weeks). The results of previously published studies have indicated that early SR of an occluded ICA may occur within 1-2 h to two weeks after occlusion (1)(2)(3)(4), and early SR of the ICA appears to be common in patients with extracranial ICA occlusion caused by arterial dissection (57-68% of the evaluated cohorts) (3,(5)(6)(7)(8). However, the incidence of late SR of an occluded ICA has been reported to be markedly lower, with 2.0 and 3.8%, respectively (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spontaneous recanalization (SR) may occur in patients with ICA occlusion, which may be further categorized as early or late SR, based on the cut-off duration of the mean hospitalization of these patients (usually two weeks). The results of previously published studies have indicated that early SR of an occluded ICA may occur within 1-2 h to two weeks after occlusion (1)(2)(3)(4), and early SR of the ICA appears to be common in patients with extracranial ICA occlusion caused by arterial dissection (57-68% of the evaluated cohorts) (3,(5)(6)(7)(8). However, the incidence of late SR of an occluded ICA has been reported to be markedly lower, with 2.0 and 3.8%, respectively (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Of occlusion due to carotid artery dissection (CAD), early recanalization is observed in 57–69% of cases. [1] CAD is a highly dynamic process with dramatic morphological changes in the early stage of the disease; however, little is known about the radiographic findings in the initial week.…”
mentioning
confidence: 99%
“…As the majority of ICA occlusions are due to atherosclerosis,[1] the differentiation between the atherosclerotic disease and CAD is important. In CAD patients, the occlusion frequently locates 2–3 cm distal to the common carotid bifurcation and has a tapered, flame-like appearance, which is consistent with the findings in CTA of our patient.…”
mentioning
confidence: 99%